Dietary intakes of dioxins and polychlorobiphenyls (PCBs) and mortality: EPIC cohort study in 9 European countries - Thibault Fiolet; Geneviève Nicolas; Corinne Casagrande; Zsuzsanna Horvath; Pauline Frenoy; Elisabete Weiderpass; Marc J. Gunter; Jonas Manjer; Emily Sonestedt; Domenico Palli; Vittorio Simeon; Rosario Tumino; et al. (International Journal of Hygiene and Environmental Health, 2024)

Diet and lifestyle in relation to small intestinal cancer risk: findings from the European Prospective Investigation into Cancer and Nutrition (EPIC) - Zeynep Ersoy Guller; Rhea N. Harewood; Elisabete Weiderpass; Inge Huybrechts; Mazda Jenab; José María Huerta; Maria-Jose Sánchez; Paula Jakszyn; Pilar Amiano; Eva Ardanaz; Claudia Agnoli; Rosario Tumino; et al. (Cancer Causes & Control, 2023)
Purpose The incidence of small intestinal cancer (SIC) is increasing, however, its aetiology remains unclear due to a lack of data from large-scale prospective cohorts. We examined modifiable risk factors in relation to SIC overall and by histological subtype. Methods We analysed 450,107 participants enrolled in the European Prospective Investigation into Cancer and Nutrition cohort. Cox proportional hazards models were used to estimate univariable and multivariable hazard ratios (HRs) and 95% confidence intervals (CIs). Results During an average of 14.1 years of follow-up, 160 incident SICs (62 carcinoids, 51 adenocarcinomas) were identified. Whilst univariable models revealed a positive association for current versus never smokers and SIC (HR, 95% CI: 1.77, 1.21–2.60), this association attenuated in multivariable models. In energy-adjusted models, there was an inverse association across vegetable intake tertiles for SIC overall (HR T3vsT1 , 95% CI: 0.48, 0.32–0.71, p-trend: < 0.001) and for carcinoids (HR T3vsT1 , 95% CI: 0.44, 0.24–0.82, p-trend: 0.01); however, these attenuated in multivariable models. Total fat was also inversely associated with total SIC and both subtypes but only in the second tertile (SIC univariable HR T2vsT1 , 95% CI: 0.57, 0.38–0.84; SIC multivariable HR T2vsT1 , 95% CI: 0.55, 0.37–0.81). Physical activity, intake of alcohol, red or processed meat, dairy products, or fibre were not associated with SIC. Conclusion These exploratory analyses found limited evidence for a role of modifiable risk factors in SIC aetiology. However, sample size was limited, particularly for histologic subtypes; therefore, larger studies are needed to delineate these associations and robustly identify risk factors for SIC.

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Prospective study of physical activity and risk of primary adenocarcinomas of the oesophagus and stomach in the EPIC (European Prospective Investigation into Cancer and nutrition) cohort - José María Huerta; Carmen Navarro; María-Dolores Chirlaque; María-José Tormo; Karen Steindorf; Genevieve Buckland; Fátima Carneiro; Nina Føns Johnsen; Kim Overvad; Jakob Stegger; Anne Tjønneland; Marie-Christine Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

Fruits and vegetables consumption and the risk of histological subtypes of lung cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) - F. L. Büchner; H. B. Bueno-de-Mesquita; J. Linseisen; H. C. Boshuizen; L. A. L. M. Kiemeney; M. M. Ros; K. Overvad; L. Hansen; A. Tjonneland; O. Raaschou-Nielsen; F. Clavel-Chapelon; M.-C. Boutron-Ruault; et al. (Cancer Causes & Control, 2010)

Serum calcium and the risk of prostate cancer - C. Halthur; A. L. V. Johansson; M. Almquist; J. Malm; H. Grönberg; J. Manjer; P. W. Dickman (Cancer Causes & Control, 2009)

Ethanol intake and the risk of pancreatic cancer in the European prospective investigation into cancer and nutrition (EPIC) - Sabine Rohrmann; Jakob Linseisen; Alina Vrieling; Paolo Boffetta; Rachael Z. Stolzenberg-Solomon; Albert B. Lowenfels; Majken K. Jensen; Kim Overvad; Anja Olsen; Anne Tjonneland; Marie-Christine Boutron-Ruault; Francoise Clavel-Chapelon; et al. (Cancer Causes & Control, 2009)

Fruit and vegetable consumption and lymphoma risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) - Sabine Rohrmann; Nikolaus Becker; Jakob Linseisen; Alexandra Nieters; Thomas Rüdiger; Ole Raaschou-Nielsen; Anne Tjønneland; Hans E. Johnsen; Kim Overvad; Rudolf Kaaks; Manuela M. Bergmann; Heiner Boeing; et al. (Cancer Causes & Control, 2007)

Alcohol intake and breast cancer risk: the European Prospective Investigation into Cancer and Nutrition (EPIC) - Anne Tjønneland; Jane Christensen; Anja Olsen; Connie Stripp; Birthe L. Thomsen; Kim Overvad; Petra H. M. Peeters; Carla H. van Gils; H. Bas Bueno-de-Mesquita; Marga C. Ocké; Anne Thiebaut; Agnès Fournier; et al. (Cancer Causes & Control, 2007)